Science and technology dean inside the 60 years of Universidad Centroccidental Lisandro Alvarado (Gestión y Gerencia, 2022)
This essay presents a summary of the history of the Dean of Sciences and Technology, framed in the 60 years of the Universidad Centroccidental Lisandro Alvarado, covering the beginnings of each of its programs, both Undergraduate and Postgraduate, its directors and pioneers. . As well as, a small description of the self-management associations that have been developed in order to achieve the generation of resources that allow the sustainability of educational programs is presented, with the vision of continuing to graduate quality professionals, required by our country and the world.
Keywords: Anniversary; Sciences and Technology Dean; History